Réponses

Meilleure réponse !
2014-09-03T14:43:51+02:00
A) (12,8) + (+ 1,2)  = 12,8 + 1,2 = 14

b) (- 12,8) + (+1,2) = - 12,8 + 1,2 = - 11,6

c) (- 12,8) + (- 1,2) = (-12,8 - 1,2 = - 14

d) (+12,8) + (- 1,2) = 12,8 - 1,2 = 11,6

e) (- 13,58) + (+ 13,58) = - 13,58 + 13,58 = 0

f) (+ 14,8) + 0 = 14,8 + 0 = 14,8
- 13,58 + 13,58 = 0
Merci
Maudmarine tu pourrais essayer de maider sur mon probleme en physique
  • Utilisateur Brainly
2014-09-03T14:46:34+02:00
(+ 12,8) + (+ 1,2)
= 12,8 + 1,2
= 14

(- 12,8) + (+ 1,2)
= - 12,8 + 1,2
= 1,2 - 12,8
= - 11,6

(- 12,8) + (- 1,2)
= - 12,8 - 1,2
= - 14

(+ 12,8) + (- 1,2)
= 12,8 - 1,2
= 11,6

(- 13,58) + (+ 13,58)
= 13,58 - 13,58
= 0

(+ 14,8) + 0
= 14,8 + 0
= 14,8